Identification and biochemical characterization of a novel carotenoid oxygenase: elucidation of the cleavage step in the Fusarium carotenoid pathway - Prado-Cabrero, Alfonso; Estrada, Alejandro F.; Al-Babili, Salim; Avalos, Javier (Wiley, 2007)
The synthesis of the acidic apo‐carotenoid neurosporaxanthin by the fungus Fusarium fujikuroi depends on four enzyme activities: phytoene synthase and carotene cyclase, encoded by the bifunctional gene carRA, a carotene desaturase, encoded by carB, and a postulated cleaving enzyme converting torulene (C40) into neurosporaxanthin (C35). Based on sequence homology to carotenoid oxygenases, we identified the novel fungal enzyme CarT. Sequencing of the carT allele in a torulene‐accumulating mutant of F. fujikuroi revealed a mutation affecting a highly conserved amino acid, and introduction of a heterologous carT gene in this mutant restored the ability to produce neurosporaxanthin, pointing to CarT as the enzyme responsible for torulene cleavage. Expression of carT in lycopene‐accumulating E. coli cells resulted in the formation of minor amounts of apo‐carotenoids, but no enzymatic activity was observed in β‐carotene‐accumulating cells, indicating a preference for acyclic or monocyclic carotenes. The purified CarT enzyme efficiently cleaved torulene in vitro to produce β‐apo‐4′‐carotenal, the aldehyde corresponding to the acidic neurosporaxanthin, and was also active on other monocyclic synthetic substrates. In agreement with its role in carotenoid biosynthesis, the carT transcript levels are induced by light and upregulated in carotenoid‐overproducing mutants, as already found for other car genes.